Управління проектами технологічних систем вирощування сільськогосподарських культур - Луб, П. М.; Шарибура, А. О.; Тригуба, І. Л.; Пукас, В. Л. (НТУ "ХПІ", 2016)
Виокремлено технологічну систему вирощування сільськогосподарських культур та означено її проектне середовище. Означено особливості управління проектами цих технологічних систем. Наведено основні складові, що впливають на ефективність реалізації цих проектів. Означено головні завдання із розроблення методів та моделей управління проектами технологічних систем вирощування сільськогосподарських культур. Окреслено практичну цінність застосування таких методів та моделей для супроводу управлінських рішень у процесах управління відповідними проектами.

The technological system of crops growing is determined. The project environment is uncategorized. The features of project management of technological systems are determined. The basic elements that influence on effectiveness of these projects are given. The need reveals for an integrated approach to project management technology systems growing crops. For this thing must make two stages of research – match the parameters of technological components and make a management decisions for project management processes during their implementation. On the basis of these provisions prove the need for the use of specific methods and models that enable to take into account the features of technological system and features of the integrated production system projects. The main objectives of methods and models developing of the technology systems of crops growing project management are given. The practical value of the use of such methods and models to support management decisions in the management of the project are outlined.
Project management of crops growing technological systems
Keywords: технічне оснащення; процеси управління; мінливість умов; методи; моделі; моделювання; ефективність; projects; technological system; equipment; management processes; variability of conditions; methods; models; simulation efficiency